THE IMPACT OF ARTIFICIAL INTELLIGENCE ON LANGUAGE LEARNING - Khumora Abduhakimova (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper explores the impact of Artificial Intelligence (AI) on language learning through a qualitative review of scholarly and professional sources. It highlights how AI tools such as speech recognition, chatbots, and personalized learning platforms enhance learner motivation, autonomy, and skill development by offering adaptive and instant feedback. While these technologies present vast opportunities for flexible and accessible education, the review also addresses potential drawbacks, including overreliance on AI and reduced human interaction. The study concludes that a balanced and critical approach is necessary to effectively integrate AI into language education.